The taxation of employees on the vesting of equity instruments: a comparative analysis between South Africa, Australia and Singapore - Nyanin, Gigi Adjoa (My University, 2021)
In South Africa, the tax rules governing employee share schemes provide that an employee, who receives shares in terms of the scheme, will have a tax liability as soon as, inter alia, all restrictions in relation to those shares are lifted, even though he/she may not have actually disposed of the shares at that particular point. This may leave the employee with a liquidity problem, should the employee not be able to dispose of the shares in order to settle the resultant tax liability. This research report considers the manner in which sections 8B and 8C of the Income Tax Act can be amended to resolve the aforementioned cash flow problems experienced by employees thereby making employee share schemes more attractive to employees. The tax laws of Australia and Singapore provide concessions that mitigate the cash flow constraints that arise when employees are required to settle the tax liabilities due upon the vesting of share awards. The question that is examined is whether improvements to sections 8B and 8C can be identified from a comparison of the respective Australian and Singaporean tax legislation. It is submitted that the: (i) deferral of the tax liability to a later date or when the shares are disposed of; and (ii) tax exemption or reduction of gains derived from an employee share scheme, will not only ensure that the employee has cash to settle the accompanying tax liability, but will enable the employee to determine the most opportune time to dispose of the shares in order to be able to pay the related tax. Further, the introduction of a start-up company concession will contribute to South Africa being viewed as an attractive investment destination that allows businesses to be more competitive in recruiting and retaining talented employees
A research report submitted to the Faculty of Commerce, Law and Management, University of Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Master of Commerce (in Taxation), 2021
Keywords: UCTD; Employee Share Schemes; Section 8C; Cash flow constraints; Tax Concessions; Qualified Employee Equity-Based Remuneration Scheme; Equity Remuneration Incentive Schemes; SDG-8: Decent work and economic growth